A Sociolinguistic Investigation of Language Choice among Yoruba - English Bilinguals of Bishop Onabanjo High School Ibadan, Oyo State, Nigeria. - Jekayinfa, O. J. (International Journal of Educational Management, 2022)
In spite of the rich social context of secondary schools as a linguistic environment, there is an observed lack of linguists' attention as evidenced by the scanty works available in sociolinguistic researches in secondary schools in Ibadan metropolis (Adekunle, 1990).This paper is motivated by the need to investigate the factors influencing the language preference and the possible sociolinguistic implications. It sets out to investigate the language choice of members of Bishop Onabanjo High School, Ibadan as a bilingual speech community.